Oligopolistic discrimination : a new theory on women and minority business ownership / Andrea Smith-Hunter - Smith-Hunter, Andrea (Faculty of Business and Management ; UiTM Press, 2000)
A number of theories have been advanced to explain the reasons, findings and revelations for differing patterns observed in the areas of women and minority business ownership. This paper begins by looking at the statistical distribution of women and minority business owners in various industries. It continues with a look at four of the theories that have been applied to women and minority business ownership. The paper ends by introducing a new theory - oligopolistic discrimination, and by explaining the statistical distribution of women and minority business owners in various industries and proposing empirical hypotheses that can later be tested.